Physical and mechanical properties of edible films made from non-exportable Ecuadorian bananas (Revista de Ciências Agroveterinárias, 2020)
This study set out to determine the physical and mechanical properties of edible films made from native starch extracted from non-exportable Ecuadorian bananas (Musa sapientum L.). The following treatments were applied: 0.5% starch - 0.25% glucose (T1), 0.5% starch - 0.5% glucose (T2), 1% starch - 0.25% glucose (T3), and 1% starch - 0.5% glucose (T4). Variables such as physicochemical properties, amylose content, maximum gelation temperature, and the morphology of native starch granules were assessed. Variables in the film, such as thickness, opacity, film solubility, and tensile strength, were also measured. The fruit used in this study was composed of 88.55% starch (dry basis, 15.35% amylose). The starch granules had a dominant ovoid morphology with an average diameter of 25 - 30 μm. The peak gelatinization temperature was 73.80 °C. The maximum value for viscosity was 3,836 cP at 86.8 °C. Films that presented good malleability, thickness, transparency, tensile strength, and low solubility were obtained from T4, which turned out to be the best treatment.
Keywords: tropical fruit; biopolymers; food coating; mechanical properties.